Deskripsi Parameter Fisiologis Normal Ternak Sapi Bali (Bos Sondaicus) di Desa Pukdale Kecamatan Kupang Timur Kabupaten Kupang - Hendrik J. C. Frans; Frans Umbu Datta; Yohanes T. R. M. R Simarmata (Program Studi Kedokteran Hewan, Universitas Nusa Cendana, 2020)
This research was conducted to know the normal physiological value of Bali cattle (Bos sondaicus) at Pukdale Village, Kupang Timur Subdistrict, Kupang Regency, in the form of body temperature, respiration frequency and pulsus frequency. Thisresearch used purposive sampling that is the method used toselect some samples that are assessed according to the purpose or problem of research in a population. The sample used is 36 bali cows, which are divided into groups of <1 year, 1-2 years and> 2 years of age group will be subdivided into sex category is males and females so that the number of samples each Group of 6 cows. Measurements will be done twice, in the morning at06:00 to 08:00 wita and in the afternoon at 16:00 to 18:00 wita. Measurements are made three times each time of sampling, then the value of the result of three times the measurement is averaged. The results showed that the normal body temperature of Balinese cattle in Pukdale Village, Kupang Timur Subdistrict of Kupang Regency is 38.1 ° C-39.3 ° C, the normal respiration frequency is 21-33 times / min and the normal pulsus frequency is 73-102 times / minute.